2020
DOI: 10.3390/ijerph17196988
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 Changed the Information Needs of Italian Citizens

Abstract: Italy was the first European country to be affected by COVID-19, facing an unprecedented situation. The reaction required drastic solutions and highly restrictive measures, which severely tested the trust of the Italian people. Nevertheless, the effectiveness of the introduced measures was not only linked to political decisions, but also to the choice of the Italian people to trust and rely on institutions, accepting such necessary measures. In this context, the role of information sources was fundamental, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 44 publications
2
26
0
4
Order By: Relevance
“…Overall, general practitioners (and community clinicians) made the greatest number of logged calls to the MNPHU. Based on results from early international studies [7][8][9] , it was anticipated that members of the public would constitute the largest contributors to PHU phone service utilization; however, this was not observed in the data.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall, general practitioners (and community clinicians) made the greatest number of logged calls to the MNPHU. Based on results from early international studies [7][8][9] , it was anticipated that members of the public would constitute the largest contributors to PHU phone service utilization; however, this was not observed in the data.…”
Section: Discussionmentioning
confidence: 98%
“…7,8 A study in Italy suggested that COVID-19 has correlated with a shift in ISB that resulted in increased uptake of, and trust in, official sources of information versus nonofficial sources compared to before the pandemic. 9 A broader review of ISB in Italy via analysis of Google search trends identified that health-related searches predominantly pertained to masks, disinfectants, symptoms, and vaccinations. 10 Studies conducted in China suggest that ISB including digital media uptake and frequent engagement with government sources, and possessing accurate risk perception were associated with increased uptake of preventative behavior practices.…”
Section: Introductionmentioning
confidence: 99%
“…Covid 19 memunculkan ketidakpastian dan perubahan yang sangat konstan sehingga kebutuhan informasi menjadi sangat penting. Informasi yang dimaksud tidak hanya dari sisi kuantitas namun juga dari sisi kualitas (Falcone & Sapienza, 2020). Kebijakan pemerintah yang diubah karena covid-19, harus segera diinformasikan kepada masyarakat dan pemangku kepentingan.…”
Section: A Pendahuluanunclassified
“…Kebijakan pemerintah yang diubah karena covid-19, harus segera diinformasikan kepada masyarakat dan pemangku kepentingan. Informasi tersebut dapat memberi rasa aman bagi masyarakat dalam hal perlindungan dari virus, penghentian penyebarannya (Gorfinkel et al, 2020) dan memungkinkan untuk membuat kondisi lebih dapat diprediksi (Falcone & Sapienza, 2020).…”
Section: A Pendahuluanunclassified
See 1 more Smart Citation